The public preferences for attributes at parks: A case study of recreational parks in Kuala Lumpur, Malaysia - Hasan Basri, Bakti; Musa, Rusmani; Rawi, Shamsul Bahrain (2011)
One of the most challenging tasks face by bureaucrats in city council, particularly in an urban area, is to make decisions on recreational parks. With high competition demand in land for projects such as housing areas,industrial and infrastructure purposes, an investment in recreational parks always seems not to be viable. This is compounded with the cost in establishing and maintains the parks. In the mean time, the parks also do not provide any monetary return to the council because, usually, no or minimal charges are imposed on visitors. Even though these arguments are not favourable to the investment in recreational parks, different conclusion could be drawn if sustainable development factor is included in the discussion. The factor explains that the environments need to be preserved without compromising its availability for future generation to use it. One way to do it is through the establishment of recreational parks. Therefore, this study is to investigate public preferences and their willingness to pay (WTP) for attributes provided at recreational parks in Kuala Lumpur (KL).Qualitative method is applied to determine the attributes and their levels, whilst the quantitative method which is Choice Experiments (CEs) is employed to investigate respondents’ preferences for these attributes.The results from the choice data indicates that respondents in KL has the highest preference for recreational facilities, followed by visitor amenities, natural attractions and information. The CEs results also show that the samples in KL are willing to pay for improvement in these attributes.